Inhibition of EPSPS overexpression of glyphosate‐resistant Lolium perenne L. with a clethodim and glyphosate mixture - Yanniccari, Marcos; Gigón, Ramón (Pest management science, 2025)
BACKGROUND Glyphosate‐resistant populations of some grass species have demonstrated high sensitivity to combinations of glyphosate and acetyl‐CoA carboxylase (ACCase)‐inhibiting herbicides. Nevertheless, it is unclear how glyphosate contributes to the control of glyphosate‐resistant plants when combined with other active ingredients such as clethodim. The current work aimed to detect if glyphosate‐resistant Lolium perenne L. biotypes associated with target‐site [5‐enolpyruvylshikimate‐3‐phosphate synthase (EPSPS)] overexpression and EPSPS mutation (P106S) as mechanisms of resistance are equally controlled by clethodim or clethodim plus glyphosate compared to a susceptible counterpart. RESULTS Plants of the EPSPS overexpression biotype were most sensitive to glyphosate when it was combined with clethodim, and the dose required to halve the maximal response (I50) calculated for glyphosate was reduced to a third. However, the ACCase inhibitor seems to be uniquely responsible for weed control in the P106S biotype. In response to clethodim, EPSPS expression was inhibited in the glyphosate‐resistant EPSPS overexpression biotype to a level like or lower than that of susceptible plants. The glyphosate plus clethodim mixture caused a 1.7‐fold increase in shikimate concentration in the leaves of susceptible and EPSPS overexpression biotypes compared to glyphosate alone. CONCLUSION The effects of glyphosate plus clethodim impact in different senses according to the mechanism of resistance involved, where the convergent action of both herbicides controlled the susceptible and EPSPS overexpression biotypes. In contrast, the P106S biotype died because of the clethodim component in the mixture. Mixing herbicides should not be considered a complete solution to herbicide resistance management, and its potential seems dependent on the resistance mechanism involved. © 2025 Society of Chemical Industry. The effects of glyphosate plus clethodim treatment impact in different senses according to the mechanism of resistance involved, where the convergent action of both herbicides controlled the susceptible and EPSPS overexpression biotypes. In contrast, the P106S biotype died as a result of the clethodim component in the mixture.